ANTIBACTERIAL ACTIVITIES OF RUKAM LEAVES (Flacourtia rukam Zoll. & Moritzi) AGAINST Staphylococcus aureus AND Escherichia coli - Henri Henri; Rahmad Lingga (JBIO: jurnal biosains (the journal of biosciences), 2021)
Traditional herbal medicines are now attracted significant attention used as the basis for modern medicines, including the plant of rukam (Flacourtia rukam) from the Flacourtiaceae family which is known by the public as medicine. This research aimed to explore the potential antibacterial activity for the plant of rukam (F.rukam) against bacterial Staphylococcus aureus and Escherichia coli. This research method was to first test the secondary metabolite content of F. rukam by using four solvents. The antibacterial activity extract from leaves of F. rukam was examined against S. aureus and E. coli. The antibacterial activity was assessed in the concentration include 20%, 40%, 60%, 80%, and 100% by disc diffusion method. Phytochemical test results such as phenolics, flavonoids, saponins, steroids, and alkaloids are secondary metabolites of the F. rukam plant. The highest zone of inhibition is at a concentration of 60% using methanol solvent, which is an average of 8.95 ± 1.84 in S. aures isolates, while the E. coli bacterial isolates have an average of 9.03 ± 0.95 . This result was different from using ethanol solvent where the highest inhibition zone was at a concentration of 20%, respectively 7.73 ± 2.79 in S. aureus isolates and 6.61 ± 2.18 in E. coli bacteria isolates. Antibacterial efficacy shown by this plant F. rukam provides a scientific basis and thus validates traditional use.